Effects of dexamethasone in traumatic brain injury patients with pericontusional vasogenic edema: A prospective-observational DTI-MRI study. Issue 43 (23rd October 2020) - Moll, Apolonia; Lara, Mónica; Pomar, Jaume; Orozco, Mónica; Frontera, Guiem; Llompart-Pou, Juan A.; Moratinos, Lesmes; González, Víctor; Ibáñez, Javier; Pérez-Bárcena, Jon
Abstract : Abstract: Cerebral edema is a frequent and serious complication in traumatic brain injury (TBI) patients. The objective is to study the effect of dexamethasone in patients with brain contusions, and to assess its effect on the vasogenic component of the pericontusional edema. Prospective-observational study to quantify, using magnetic resonance imaging, the volume of the edema before and after 10 days of dexamethasone in patients with brain contusions. Using diffusion tensor imaging, we have examined the effect of dexamethasone on fractional anisotropy (FA) and apparent diffusion coefficient (ADC). To assess changes, the pre- and post-treatment values for each patient were compared using a paired-samples Student t test. We included 30 TBI patients, 15 in each group. The volume of the vasogenic edema in the group of patients treated with dexamethasone decreased from 22 to 19 mL and this decrease was statistically significant ( P < .05). Nevertheless, in the non-steroids group the volume of the vasogenic edema increased from 11 to 15 mL. There was a significant decrease in the ADC value (from 1.78–1.59; P < .05); and a significant increase in the FA value (0.09–0.11; P < .05) in the patients treated with dexamethasone. Using diffusion tensor imaging we have shown in a selected group of TBI patients with vasogenic pericontusional edema, a reduction of edema volume, a decrease in the ADC and an increase in the FA after treatment with dexamethasone. However, we have no data if such results are beneficial in terms of improving functional outcome.